Hussein Chalayan - Clark, Judith, 1967- (Rizzoli, 2011)
"The comprehensive book on the visionary Hussein Chalayan, one of the most innovative, experimental, and conceptual fashion designers working today. Internationally acclaimed, Hussein Chalayan is known for his inventive use of materials and integration of new technology into his designs. He is also celebrated for putting the creative process itself on view. Some of his best-known designs include a paper dress that can be folded into an envelope and airmailed, armchair covers that transform into dresses, and a coffee table that reveals itself to be a wooden skirt. Original and groundbreaking, his designs are also pretty and modern, and this book explores that continuum. Featuring Chalayan's complete body of fashion and creative work--including his installations, videos, and photographs"-- Vydavatelská anotace
Keywords: Chalayan, Hussein, -- 1970-; monografie; monographs; 20.-21. století; módní návrháři -- Velká Británie -- 20.-21. století; fashion designers -- Great Britain -- 20th-21st centuries